Cutting performance of deep cryogenic treated and nitrided HSS cutting tool inserts - Šolić, Sanja, inženjerka strojarstva; Schauperl, Zdravko; Tropša, Vlado (2019)
High speed steel (HSS) is a very important industrial tool material and has been constantly improved for different wear resistance applications and cutting tools, i.e. drills, milling cutters, hobs and for the cutting tools in which the economical cutting speed is too low for choosing the carbide tools. The properties of HSS depend significantly on the parameters of the conducted heat treatment. In this paper, the influence of deep cryogenic treatment in combination with nitriding of metallurgical powder metallurgy HSS on the wear resistance was measured. Additionally, the cutting performance in a single point cutting tool machinability test at the configuration of the dry low-speed turning of steel was investigated. The results showed that deep cryogenic treatment itself, and in combination with nitriding, resulted in the reduction of the wear rate. The results of the single point cutting tool machinability test showed that deep cryogenic treated and nitrided HSS inserts performed worse than the classically heat-treated inserts and deep cryogenic treated HSS inserts exhibited approximately the same flank wear as the nitrided ones.
Bibliografija: 21 jed.
Abstract.
Keywords: Alati za rezanje -- Brzorezni čelik -- Kriogena obrada -- Otpornost